The diversity of the catalytic properties of class A beta-lactamases. - Matagne, A (1990)
The catalytic properties of four class A beta-lactamases were studied with 24 different substrates. They exhibit a wide range of variation. Similarly, the amino acid sequences are also quite different. However, no relationships were found between the sequence similarities and the substrate profiles. Lags and bursts were observed with various compounds containing a large sterically hindered side chain. As a group, the enzymes could be distinguished from the class C beta-lactamases on the basis of the kappa cat. values for several substrates, particularly oxacillin, cloxacillin and carbenicillin. Surprisingly, that distinction was impossible with the kappa cat./Km values, which represent the rates of acylation of the active-site serine residue by the beta-lactam. For several cephalosporin substrates (e.g. cefuroxime and cefotaxime) class A enzymes consistently exhibited higher kappa cat. values than class C enzymes, thus belying the usual distinction between 'penicillinases' and 'cephalosporinases'. The problem of the repartition of class A beta-lactamases into sub-classes is discussed.